A review on intense pulsed light process as post-treatment for metal oxide thin films and nanostructures for device application. (2nd July 2022) - Noh, Youngwook; Kim, Gyu Young; Lee, Horim; Shin, Jaehak; An, Kunsik; Kumar, Manoj; Lee, Dongjin
Abstract: The intense pulsed light (IPL) post-treatment process has attracted great attention in the device fabrication due to its versatility and rapidity particularly for solution process functional structures in devices, flexible/printed electronics, and continuous manufacturing process. The metal oxide materials inherently have multi-functionality and have been widely used in form of thin films or nanostructures in device application such as thin film transistors, light emitting diodes, solar cells, supercapacitors, etc. The IPL treatment enhances the physical and/or chemical properties of the functional metal oxide through photothermal effects. However, most metal oxides are transparent to most range of visible light and require more energy for post-treatment. In this review, we have summarized the IPL post-treatment processes for metal oxide thin films and nanostructures in device applications. The sintering and annealing of metal oxides using IPL improved the device performances by employing additional light absorbing layer or back-reflector. The IPL process becomes an innovative versatile post-treatment process in conjunction with multi-functional metal oxides in near-future device applications.